Cytomegalovirus infection and associated hospitalization and costs among individuals undergoing allogeneic hematopoietic stem cell transplant. (2nd January 2020) - Schelfhout, Jonathan; Brown, Harold; House, John A.; Raval, Amit D.
Abstract: Objective: This study utilized a large, national US database to explore the impact of Cytomegalovirus (CMV) infection on hospital services utilization and costs during the first 100 days following allogeneic hematopoietic stem cell transplant (allo-HSCT). Methods: This retrospective, observational cohort study used data from the Premier Healthcare database to identify patients undergoing their first (index) allo-HSCT procedure between 1 January 2006 and 31 March 2015. Three subgroups were analyzed according to CMV-related readmissions during the 100-day follow-up (0, 1, or 2+ readmissions) to compare healthcare utilization and costs. Results: A total of 1610 patients (mean age, 50.5 years; 56.9% male) from 52 US hospitals met the inclusion criteria. During follow-up, 212 (13.2%) patients had 1 ( n  = 161; 10.0%) or 2+ ( n  = 51; 3.2%) CMV-related readmissions. The mean ± SD number of all follow-up encounters (inpatient admissions and hospital-based outpatient visits) was similar for the no CMV (3.9 ± 3.9), 1 CMV (3.7 ± 3.9), and 2+ CMV (4.5 ± 3.8) readmission groups ( p  = .439). Mean total costs of hospital-based healthcare encounters (inpatient admissions and hospital-based outpatient visits) during follow-up were significantly greater in patients who had a CMV readmission ($111, 729 [1 CMV readmission]; $184, 021 [2+ CMV readmissions]) compared to those without a CMV readmission ($46, 064; p  < .001]. 100-day follow-up mortality was higher in the CMV vs. non-CMV readmission groups (30.2 vs. 8.2%; p  < .001). Conclusions: This large, national database study revealed significantly higher healthcare utilization and costs, as well as mortality, among patients with CMV-related re-hospitalization during the first 100 days post-transplant as compared to patients without CMV-related hospitalization.